Is Virtual Reality Training More Effective Than Traditional Physical Training on Balance and Functional Mobility in Healthy Older Adults? A Systematic Review and Meta-Analysis - Liu, Meng; Zhou, Kaixiang; Chen, Yan; Zhou, Limingfei; Bao, Dapeng; Zhou, Junhong (Frontiers in Human Neuroscience, 2022)
Objective: Studies showed the benefits of virtual reality training (VRT) for functional mobility and balance in older adults. However, large variance in the study design and results is presented. We here thus completed a systematic review and meta-analysis to quantitatively examine the effects of VRT on functional mobility and balance in healthy older adults. METHODS: We systematically reviewed the publications in five databases. Studies examining the effects of VRT on the measures of functional mobility and balance in healthy older adults were screened and included if eligible. Subgroup analyses were completed to explore the effects of different metrics of the intervention design (e.g., session time) on those outcomes related to functional mobility and balance. Results: Fifteen studies of 704 participants were included. The quality of these studies was good. Compared to traditional physical therapy (TPT), VRT induced greater improvement in TUG (MD = -0.31s, 95%CI = -0.57 to -0.05, P = 0.02, I2 = 6.34%) and one-leg eyes-open stance (OLS-O) (MD =7.28s, 95%CI = 4.36 to 10.20, P = 0.00, I2 = 36.22%). Subgroup analyses revealed that immersive VRT with more than 800 minutes of total intervention time over eight weeks and at least 120 minutes per week, and/or designed by the two motor learning principles was optimal for functional mobility and balance. Conclusion: VRT can significantly improve functional mobility and balance in healthy older adults compared to TPT, and the findings provided critical knowledge of the optimized design of VRT that can inform future studies with more rigorous designs.